PREVENTIVE MAINTENANCE OF THE GATE VALVE MOV 30, UNIT 7, AT PT. INDONESIA POWER SURALAYA PGU - Haafizh, Husain; Erwin, Erwin; Yusuf, Yusvardi; Setiawan, Ipick; Susilo, Sidik; Waloyo, Hery Tri; Jannah, Miftahul (Trends in Mechanical Engineering Research, 2025)
One of the important components in the power generation process at the Suralaya PGU PLTU is the Gate Valve. The MOV 30 Gate Valve is a valve that functions to regulate the flow of steam gas from the extraction steam to the blow down tank. Preventive maintenance on the MOV 30 Gate Valve unit 7 aims to prevent unwanted damage, reduce the risk of failure, and ensure that the device operates with maximum efficiency. With proper preventive maintenance, PT Indonesia Power hopes to avoid disruptions in power generation operations, minimize downtime, and extend the operational lifespan of the equipment. Damage to a gate valve can be caused by several factors, including excessive pressure in the valve flow, high temperatures passing through the valve, and friction forces when opening and closing the valve.